Planning, implementation, and evaluation of educational intervention based on PRECEDE-PROCEED model for mothers about oral health promotion on children aged 3-6 years - Narges Bab; Hassan Khodadadi; Mostafa Nasirzadeh (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Mothers play an important role in oral health of children. The present study was planned, implemented, and evaluated to determine the impact of mothers' educational program based on PRECEDE-PROCEED model on oral health promotion of Rafsanjan 3-6-year-old children, in 2020. MATERIALS AND METHODS: This quasi-experimental study was conducted on 100 mothers with children aged 3-6 years divided into two groups. The research tool was developed and approved based on the model phases in the form of demographic information, predisposing, enabling, and reinforcing factors. At phase five, intervention planning was conducted and the program was implemented in four sessions (45 min each) in 30 days. Follow-up was done 2 months after the last training session. The data were analyzed by SPSS18, using Chi-square, paired t-test, and independent t-test at the significance level of 0.05. RESULTS: After implementing the program, a significant difference was observed between predisposing, enabling, and reinforcing factors, as well as oral health-related behaviors of the two groups (P < 0.05). Finally, 30.4% of the changes in oral health-related behavior resulted from the implementation of the designed educational program. CONCLUSION: Considering the importance of planning to promote children's oral health and hygiene, it is recommended that the PRECEDE-PROCEED model be used to design, implement, and evaluate health evidence-based interventions.